Hubungan Pengetahuan dan Pendapatan Keluarga dengan Kejadian Stunting pada Balita di Puskesmas Rantau Selamat Aceh Timur Tahun 2024 - Dina Saputri; Ester Simanullang (Inovasi Kesehatan Global, 2025)
The incidence of stunting in toddlers is one of the global nutritional problems. Based on UNICEF data from 2010–2017, it shows that the prevalence of stunting in the world reached 28%, in Eastern and Southern Africa it was 40%, and in South Asia it was 38%. When compared with the "non-public health problem" limit according to WHO for stunting problems of 20%, almost all countries in the world experience public health problems. The aim of the research is to determine the relationship between knowledge and family income and the incidence of stunting among toddlers at the Rantau Selamat Community Health Center, East Aceh in 2024. This type of research is analytical observational research using a cross-sectional approach, the sample is some of the toddlers at the Rantau Selamat Community Health Center, East Aceh in 2024, a number of 61 respondents. Research results: There is a relationship between knowledge and income and the incidence of stunting in toddlers in the Rantau Selamat Community Health Center Working Area, East Aceh in 2024. It is recommended for the Community Health Center to provide education to parents so that they have good knowledge of skills in parenting toddlers, and to the local community Those who are pregnant need to pay attention to their diet to prevent LBW. For parents to monitor the growth and development of their children under five so that stunting can be prevented and overcome.